2018
DOI: 10.1111/apa.14599
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal birth cohort study found that a significant proportion of children had abnormal metabolic profiles and insulin resistance at 6 years of age

Abstract: Aim Metabolic syndrome represents a cluster of risk factors for cardiovascular disease, and we investigated whether otherwise healthy 6‐year‐olds showed metabolic alterations. Methods This study followed up a representative Swedish population‐based cohort of full‐term infants recruited on the maternity ward at Hallands Hospital Halmstad, Sweden, from 2008 to 2011. They were examined at a mean of 6.6 years of age (range 6.5–6.9) using various measures for signs of metabolic syndrome. Results One key measure sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…This finding comes from a longitudinal study that was conducted in Halland, south‐west Sweden, by Kjellberg et al. . They found that 26% of the 212 children in the study had abnormal metabolic profiles, including insulin resistance.…”
Section: Many Seemingly Healthy Children Show Signs Of Metabolic Syndmentioning
confidence: 99%
“…This finding comes from a longitudinal study that was conducted in Halland, south‐west Sweden, by Kjellberg et al. . They found that 26% of the 212 children in the study had abnormal metabolic profiles, including insulin resistance.…”
Section: Many Seemingly Healthy Children Show Signs Of Metabolic Syndmentioning
confidence: 99%
“…Emma Kjellberg receives the award for her paper Longitudinal birth cohort study found that a significant proportion of children had abnormal metabolic profiles and insulin resistance at 6 years of age . The authors conducted a longitudinal study in Halland, south‐west Sweden, to investigate whether otherwise healthy six‐year‐olds showed metabolic alterations that could increase their risk for cardiovascular disease.…”
mentioning
confidence: 99%
“…The study by Kjellberg et al. in this issue of Acta Paediatrica makes an important contribution to the field, because it reports on the metabolic risk factors in a population‐based cohort of more than 200 healthy six‐year‐old Swedish children born at full term. The data demonstrate that 26% of the investigated children had at least one risk factor and that 7% had two or more risk factors on a level that required action, according to the European identification and prevention study mentioned above .…”
mentioning
confidence: 99%
“…In their study, Kjellberg et al. demonstrated that all the children in the cohort with at least two metabolic risk factors had a high waist circumference. They also concluded that waist circumference was a better indicator of insulin resistance than body mass index.…”
mentioning
confidence: 99%
See 1 more Smart Citation